Drug Induced Encephalopathy in Patients with Chronic Kidney Disease: A Case Series (BIRDEM Medical Journal, 2018)
Drug induced encephalopathy is an established side effect of many drugs when used in a higher dose. Though we do not encounter this side effect frequently in our day to day practice, yet with renal impairment this is not uncommon. Even with a reduced dose many of these can precipitate encephalopathy in this special group of patients. We are presenting here a series of seven such cases of drug induced encephalopathy in patients with renal impairment.Birdem Med J 2018; 8(2): 172-176